2017
DOI: 10.1515/rnam-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Fast topological-shape optimization with boundary elements in two dimensions

Abstract: Wide variety of engineering design tasks can be formulated as constrained optimization problems where the shape and topology of the domain are optimized to reduce costs while satisfying certain constraints. Several mathematical approaches were developed to address the problem of finding optimal design of an engineered structure. Recent works [1,2] have demonstrated the feasibility of boundary element method as a tool for topological-shape optimization. However, it was noted that the approach has certain drawba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The level of details in the final solution depends on the threshold of the topological derivative and the number of iterations. However, both obtained solutions are in qualitative agreement with 2D and 3D solutions of similar problems obtained earlier [15,16,23]. The quality of the surface of the optimal configuration is improved with Laplassian smoothing [24] post-processing step.…”
Section: Numerical Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The level of details in the final solution depends on the threshold of the topological derivative and the number of iterations. However, both obtained solutions are in qualitative agreement with 2D and 3D solutions of similar problems obtained earlier [15,16,23]. The quality of the surface of the optimal configuration is improved with Laplassian smoothing [24] post-processing step.…”
Section: Numerical Resultssupporting
confidence: 81%
“…Since the surface solution is found, the solution in stresses at internal points is found via PVFMM summation of the kernels 5, 6. It is worth noting here, that the sampling of the points inside the domain should not necessarily be uniform -one could successfully use adaptive strategies of sampling points inside the domain, which reduces the computational complexity of the domain computation to O(N s ), where N s is the number of surface elements [15].…”
Section: A X B Ymentioning
confidence: 99%
See 1 more Smart Citation
“…In our earlier works [23,24] we have demonstrated that if the change in boundary configuration at every iteration is relatively small (Fig. ( 5) (B)), one can use fast update techniques for the volume and surface solutions, which would be faster than full re-computation of the BVP.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…These early works demonstrated conceptual applicability of BEM in combination with a hard-kill algorithm of material removal to the problems of topology optimization. The first applications of algebraically accelerated BEM to two-and tree-dimensional problems of elasticity were presented in our papers [23,24]. In these works we used Shur complements [36] for fast updates of the BVP solution [23], and H 2 -matrices for fast solutions of the BVP [24].…”
Section: Related Workmentioning
confidence: 99%